Toxicity testing using hematopoietic stem cell assays. (November 2007) - Clarke, E; Pereira, C; Chaney, R; Woodside, S; Eaves, AC; Damen, J
For over 40 years, in vitro assays have been used to understand the complex system of hematopoiesis. Now, several of these assays are undergoing resurgence as scientists in academia and industry are discovering how these assays can be utilized in drug discovery and development. These assays use primary cells from various hematopoietic tissues in multiple species to provide high content information. While conditions in the human body cannot be completely reproduced in vitro, hematopoietic colony-forming cell assays are proving to be a clinically relevant tool to evaluate potential toxic effects of new compounds. The ability to use these assays as a replacement of, or in conjunction with, high-throughput screening assays and high priced in vivo assays can improve the success of the decision-making process, saving time and costs during drug development.